Circulation of picobirnavirus in Neotropical free-ranging mammals - Vanderhoeven, Ezequiel; Paresque, Roberta; Mello, Iago; Nates, Silvia; Vicentini, Fernando; Díaz, Adrián; Masachessi, Gisela (Veterinary research communications, 2024)
Picobirnavirus (PBV) is a family of non-enveloped double-stranded RNA viruses with bisegmented genomes. Segment 1 encodes the capsid protein and segment 2 encodes RNA-dependent RNA polymerase. They exhibit high genomic heterogeneity and infect a wide range of vertebrate hosts, including humans. The objective of this study was to expand our knowledge of the circulation of PBV in free-living animals from two regions (Brazil and Argentina) of the Atlantic Forest. Fecal samples were analyzed from free-living animals: tapir, brocket deer, peccary, and different species of rodents and marsupials. A total of 133 samples were collected and analyzed by RT-PCR, of which 44 (33.08%) were PBV-positive. Nine amplicons were sequenced, five species from Argentina and four from Brazil, and phylogenetic analysis was performed. The nucleotide and amino acid identities of the PBV strains detected in animals from Argentina and Brazil were between 66.3% and 82.5% and between 55.3% and 74.2%, respectively. The analysed strains presented conserved nucleotide blocks without distinction of the host species. The phylogenetic tree showed that PBV strains from Atlantic Forest animals belonging to genogroup I were grouped into different clusters, without defining groups according to host species (human or animal) or the geographical area of detection. This is the first study on PBV in free-living animals in the Atlantic Forest. Our analysis suggested that PBV strains can infect different animal species, leading to PBV transmission between animals and humans. This reinforces the hypothesis of previous crossover points in the ecology and evolution of heterologous PBV strains.